Development and validation of a complex intervention: A physical exercise programme aimed at delaying the functional decline in frail older adults - Rita Santos‐Rocha; Joana Freitas; Fátima Ramalho; Nuno Pimenta; Filipa Costa Couto; João Apóstolo (Wiley, 2020)
Abstract Aim To develop and validate a physical exercise programme aimed at delaying the functional decline in frail older adults. Design The revised guideline of Criteria for Reporting the Development and Evaluation of Complex Interventions in health care was followed. Methods The physical exercise programme was designed and validated by exercise specialists to be implemented by healthcare professionals. The physical exercise programme underwent three stages of development, piloting and evaluation. It includes a portfolio of exercises in different support materials (posters, e‐book and website). A testing intervention was delivered to the target population. Results The Criteria for Reporting the Development and Evaluation of Complex Interventions in health care process has the potential to help practitioners in developing and planning complex interventions, such as an exercise programme. Its components can be adjusted to the context and to the characteristics of the target population. A study protocol and a pilot study will be developed to test the effectiveness of the physical exercise programme on delaying the functional decline of frail older adults.